Effect of N, P and K fertilizer on the flower yield of Chrysanthemum - Ahmed, R; Hussain, MJ; Ahmed, S; Karim, MR; Siddiky, MA (The Agriculturists, 2017)
An experiment was conducted at the research field of Horticulture Research Centre, BARI, Gazipur during Rabi season of 2012-13 to 2014-15 to evaluate the response of different doses of N, P and K on the yield and yield attributes of chrysanthemum (var. BARI Chrysanthemum-1) and to find out the optimum and economic doses of NPK for maximizing yield of chrysanthemum. Treatments comprising four levels each of N (0, 100, 150 and 200 kg ha-1), P (0, 50, 75 and 100 kg ha-1) and K (0, 90, 135 and 180 kg ha-1) along with blanket dose of 2 kg B and 4 kg Zn ha-1 were used. The treatments were assigned in a randomized complete block design with three replications. The combined effect of NPK significantly increased yield and yield attributes of chrysanthemum for each of the yearly experiments as well as the average of three years results. Significantly, the highest flower yield (12.45, 11.47 and 11.96 t/ha) was obtained with the application of N150P75K135 kg ha-1 (T3) along with blanket dose of 2 kg B and 4 kg Zn ha-1 for the years of 2012-13, 2013-14 and 2014-15, respectively and it was statistically identical with T4 (N200P75K135 kg ha-1) treatment. Application of 150 kg N, 75 kg P and 135 kg K increased yield by 52.76, 42.29 and 36.51%, 152.08, 126.23 and 99.13% and 88.35, 51.30 and 60.75%, respectively, over their control in respect to the years. The highest benefit-cost ratio 5.54 followed by 5.14 was obtained from T3 (N150P75K135 kg ha-1) followed by T4 treatment, respectively. From the quadratic regression equation averaging three years data the optimum and economic doses 155 and 151.8 kg N, 79.3 and 77.68 kg P and 118.75 and 115.7 kg K, respectively were found which could be recommended for chrysanthemum production in Grey Terrace Soil of Joydebpur under AEZ 28. The Agriculturists 2017; 15(1) 58-67